Key Signatures of Magnetofossils Elucidated by Mutant Magnetotactic Bacteria and Micromagnetic Calculations. Issue 1 (18th January 2022) - Amor, Matthieu; Wan, Juan; Egli, Ramon; Carlut, Julie; Gatel, Christophe; Andersen, Ingrid Marie; Snoeck, Etienne; Komeili, Arash
Abstract: Magnetotactic bacteria (MTB) produce single‐stranded or multi‐stranded chains of magnetic nanoparticles that contribute to the magnetization of sediments and rocks. Their magnetic fingerprint can be detected in ancient geological samples and serve as a unique biosignature of microbial life. However, some fossilized assemblages bear contradictory signatures pointing to magnetic components that have distinct origin(s). Here, using micromagnetic simulations and mutant MTB producing looped magnetosome chains, we demonstrate that the observed magnetofossil fingerprints are produced by a mixture of single‐stranded and multi‐stranded chains, and that diagenetically induced chain collapse, if occurring, must preserve the strong uniaxial anisotropy of native chains. This anisotropy is the key factor for distinguishing magnetofossils from other populations of natural magnetite particles, including those with similar individual crystal characteristics. Furthermore, the detailed properties of magnetofossil signatures depend on the proportion of equant and elongated magnetosomes, as well as on the relative abundances of single‐stranded and multi‐stranded chains. This work has important paleoclimatic, paleontological, and phylogenetic implications, as it provides reference data to differentiate distinct MTB lineages according to their chain and magnetosome morphologies, which will enable the tracking of the evolution of some of the most ancient biomineralizing organisms in a time‐resolved manner. It also enables a more accurate discrimination of different sources of magnetite particles, which is pivotal for gaining better environmental and relative paleointensity reconstructions from sedimentary records. Plain Language Summary: Magnetotactic bacteria (MTB) produce chains of magnetic nanoparticles that contribute to the magnetization of sedimentary rocks. Fossilized chains can be detected in ancient geological samples using magnetic measurements. They provide unique evidence for microbial life. However, remains of fossil MTB possess ambiguous magnetic properties that make their detection problematic. Here, we demonstrate, with the help of numerical simulations and a modified MTB producing looped chains, that the magnetic properties of MTB‐rich sediments can be explained by a combination of chains made of single and multiple strands, and that chain collapse in the sediment, if occurring, likely preserves key magnetic properties, enabling the identification of fossil MTB. These properties also depend on the proportion of equidimensional and elongated magnetosomes, as well as on the relative abundances of single‐ and multi‐stranded chains. This work has important implications, as it provides new data to differentiate distinct MTB types according to their chain and magnetosome morphologies, enabling the tracking of the evolution of some of the most ancient mineral‐producing organisms. It also enables a more accurate discrimination of different sources of magnetite particles, which helps gain better environmental and relative paleointensity reconstructions from sedimentary records. Key Points: Fossilized magnetotactic bacteria in sediments bear magnetic signatures associable with different sources of magnetite particles Single‐stranded, multi‐stranded, and fold‐collapsed magnetosome chains explain all observed signatures of fossilized magnetotactic bacteria We provide criteria for the discrimination of distinct populations of ancient magnetotactic bacteria